Multi-Index Evaluation of Flexible Pavement Performance: A Comparative Analysis of PCI, IRI, and SDI Approaches - Akbardin, Juang; Cindikiawati, Fahira; Mohamad Ma’soem, Dadang (Universitas Ibn Khaldun Bogor, 2026)
The Trans-Sumatra Highway is a national road that stretches from the north to the south of Sumatra Island. The Tanjung Kemuning-Linau Road is part of the West Sumatra Trans-Sumatra Road located in Kaur Regency. This road is the main axis road of Bengkulu Province. Its function as a national road does not make the Tanjung Kemuning-Linau Road free from road damage. Therefore, an evaluation of the pavement condition is needed to restore the stability of the road in order to achieve the purpose of the road as an important infrastructure in various aspects. The purpose of this study was to identify the types of damage with the level of damage to flexible pavement, and to determine the pavement condition index based on the PCI (Pavement Condition Index) method as the main method, and the IRI (International Roughness Index) method and SDI (Surface Distress Index) as a comparative method. The case study in this study was limited to a 5 km road section, namely at KM 17+500 to 22+500. Based on the research results, the most common types of damage found were crocodile skin cracks, longitudinal cracks, and patches. The PCI method pavement condition index had an average of 39.90 in the Normal direction, and an average of 41.82 in the Opposite direction. Based on the IRI method, the average in the Normal direction was 8.17 m/km and 7.66 m/km in the Opposite direction. The results of both methods showed that the pavement condition was included in the Light Damage class. This is in line with the pavement index based on the SDI method, which had an average of 81.67 in the Normal direction and 80.20 in the Opposite direction which is also classified as light damage. To restore road stability, road improvement efforts are needed in the form of adding a surface layer / overlay. With CESA for a 10-year design life in 2033 of 13,605,740, the appropriate overlay thickness is 10 cm thick. Another road improvement option is to replace flexible pavement with composite pavement. Based on the cumulative calculation of the vehicle axle group in 2063 of 13,139,243.62, the appropriate pavement thickness for a design life of 40 years is 5 cm of asphalt concrete as the surface layer, 26.5 cm of cement concrete, and 10 cm of the base layer (LMC).